ANALISIS PENGARUH PENYALURAN ZIS TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2016 - 2021 - Zaky, Mu'ammar; Nurul Badriyah (Islamic Economics and finance in Focus, 2024)
This The objective of this research is to analyze the partial and simultaneous effects ZIS (zakat, infaq, and sadaqah) distribution, inflation, and exchange rate on economic growth in Indonesia during the 2016-2021 period. This quantitative study uses time-series secondary data during the span of 2016 to 2021, which was analyzed using multiple linear regression and classical assumption test. The results indicate that ZIS distribution, inflation, and exchange rate partially have positive and significant effects on economic growth in Indonesia and that they simultaneously have significant impacts on economic growth in Indonesia. Further, the adjusted R2 value demonstrates that the three variables above are able to explain Indonesia’s economic growth by 66.4%. The remaining 33.6% or 0.336 is explained by other variables not included in this research. Keywords: multiple linear regression, inflation, exchange rate, zakat distribution, economic growth, time series